Prevalence of Malnutrition in Orally and Tube-Fed Elderly Nursing Home Residents in Germany and Its Relation to Health Complaints and Dietary Intake - Dorothee Volkert; Lioba Pauly; Peter Stehle; Cornel C. Sieber (Gastroenterology Research and Practice)
Objective. To investigate the prevalence of malnutrition in orally and tube-fed nursing home (NH) residents in Germany and its relation to common health complaints and dietary intake. Methods. In 350 NH residents, subjects' characteristics, Mini Nutritional Assessment (MNA), and several health problems were inquired with the nursing staff using standardised interviews. In a subset of 122 residents, dietary intake was assessed by 3-day weighing records. Results. 7.7% of the participants were tube fed. 24.1% of orally nourished and 57.7% of tube-fed residents were malnourished (MNA < 17 p.). Malnutrition was significantly related to nausea/vomiting, constipation, pressure ulcers, dehydration, infections, antibiotic use, and hospitalisation. Mean daily energy intake was 1535 ± 413 kcal and mean protein intake was 54.2 ± 0.9 g/d irrespective of the nutritional state. Conclusion. In Germany, malnutrition is widespread among NH residents and is related to common health problems. The MNA rather reflects health condition than currently reduced dietary intake.